2018
DOI: 10.29252/ijop.12.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dust-Ion Acoustic Waves in a Magnetized Collisional Dusty Plasma with Kappa Distribution Function for Electrons

Abstract: The propagation of arbitrary amplitude dust ion acoustic waves (DIAWs) in a magnetized collisional dusty plasma including hot electrons, with kappa velocity distribution for electrons, warm ions and dust particles has been studied. In the presence of immobile massive dust particulates, DIAWs have been investigated through the Sagdeev pseudopotential method. It is demonstrated that the amplitude and width of the pseudo-potential are increased with the ion density and also with Directional cosines. It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Das [49] has studied the propagation characteristics of the dust ion acoustic solitary waves in dusty plasma with Boltzmann electrons and found the streaming of dust for both compressive and rarefactive KdV solitons. Zahed et al [50] have found in their study that the amplitude and width of the pseudo-potential have increased with increasing ion. Ferdousi et al [51] have theoretically investigated the characteristic properties of obliquely propagating IASWs in the presence of ambient magnetic field in nonthermal plasma.…”
Section: Introductionmentioning
confidence: 91%
“…Das [49] has studied the propagation characteristics of the dust ion acoustic solitary waves in dusty plasma with Boltzmann electrons and found the streaming of dust for both compressive and rarefactive KdV solitons. Zahed et al [50] have found in their study that the amplitude and width of the pseudo-potential have increased with increasing ion. Ferdousi et al [51] have theoretically investigated the characteristic properties of obliquely propagating IASWs in the presence of ambient magnetic field in nonthermal plasma.…”
Section: Introductionmentioning
confidence: 91%